(3SQGL Gdedhc hGdNdaGA hefgGL GdhdGI hGdCeQGAs - (3GdWQWhTj , eMeO Hf GdhdjO Hf eMeO Hf Nda GdbQTj GdagQj, CHh HcQ,J (B520 (3g` s
(3ChdgG (B:s
(3CeG HYO aEfi deG fXQJ ai SjQ GdCee GdeGVji hGdedhc dhLOJ Pdc fhYjf GMcGekG hSjGSGJ aGeG GdCMcGe GdeTJedI Ydi eG GYJbOhg Hjf GdMdGd hGdMQGe hGdHjhY hGdCfcMI s
(3BNQgG (B:s
(3aEf bdJ CehGJ adSJ cGPH hEf bdJ CMjG adSJ Je GdcJGH s
(3HChdgG fbhd eNJdaI hHNWhW eNJdaIs
(3HgG WeS COi Edi VjGY LRA ef GdHOGjIs
(3fSNI KGfjI s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdSjGSI hGdGLJeGYs